Myocardial T1 mapping: where are we now and where are we going? - Abdel-Gadir A; Treibel TA; Moon JC (Research Reports in Clinical Cardiology, 2014)
Amna Abdel-Gadir,1,2 Thomas A Treibel,1,2 James C Moon1,2 1The Heart Hospital Imaging Centre, University College London Hospitals, London, UK; 2Institute of Cardiovascular Science, University College London, London, UK Abstract: Cardiovascular magnetic resonance offers noninvasive myocardial tissue characterization as a key unique strength over other imaging techniques. In particular T1, a tissue property that alters with disease, has gained prominence as a diagnostic tool. Prior to the administration of contrast, the native T1 changes with a number of processes such as fibrosis, edema, and infiltration. If a post-contrast scan is also acquired, the post-contrast T1 and extracellular volume fraction can be measured. Detecting and quantifying early and established myocardial pathological processes permits better diagnosis, prognostication, and tracking of therapy. Keywords: extracellular volume fraction, diffuse fibrosis, interstitium, cardiac remodeling, myocardial intracellular volume